Effect of Simvastatin on Eosinophilic Inflammation of Bladder Tissue in Interstitial Cystitis Rat Model - Muhamad Nur Syukriani Yusuf; Abdi Dzul Ikram Hasanuddin; Zuhriana K Yusuf; Trinny Tuna; Nurani Ibrahim; Marshanda Tiara Posumah; Ridho Tianggara (Jurnal Kedokteran Brawijaya, 2022)
In the urogenital system, simvastatin is associated with interstitial cystitis adverse effects, but the exact mechanism is not yet clearly defined. This study aims to determine the effect of simvastatin on eosinophilic inflammation of bladder tissue in vivo. Laboratory experimental research design with the post-test only control group using 24 female Wistar rats aged 8-10 weeks were randomly divided into simvastatin 50mg/kg BW (n=12) or placebo carboxymethylcellulose 0.5% (n=12). All groups received treatment through oral gavage for thirty days. After that, each group was divided equally into three subgroups: control rat, day 0 Interstitial Cystitis (IC) rat (IC0), and day 3 IC rat (IC3). Control or IC0 rats each received intravesical instillation of buffered saline or protamine sulfate (PS), respectively, and were terminated immediately less than 3 hours after instillation. The IC3 rats received intravesical PS instillation and were terminated three days post-instillation. The bladder tissue was made in Hematoxylin-Eosin histology preparations. As in previous studies, the results showed successful desquamation of the urothelium after PS instillation. Tissue eosinophil counts were significantly higher in the simvastatin group than in the placebo group in the IC3 model (15.50±5.92 vs. 4.00±2.83, p=0.013). It can be concluded that the mechanism of the adverse effect of simvastatin on bladder tissue is through increased tissue inflammation mediated by eosinophils along with urothelial layer destruction by the protamine sulfate.